Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/pssa.2210980119
|View full text |Cite
|
Sign up to set email alerts
|

Different Etch Pit Shapes Revealed by Molten KOH Etching on the (001) GaAs Surface and Their Dependence on the Burgers Vectors

Abstract: It is found that the etch pits revealed by molten KOH etching on the (001) GaAs surface have definitely different shapes depending on the Burgers vectors of the dislocations. The round hexagonal etch pit corresponds to a dislocation with Burgers vector of ½a〈101〉 inclined to the (001) plane, while the small round square etch pit corresponds to a dislocation with Burgers vector of ½a〈110〉 parallel to the (001) plane It is suggested that the larger hexagonal etch pit is associated with parallel pair of partial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…He also developed an etch pit reagent and to analyze the effects of thermal stress on the shapes and sizes of etch pits in thallium arsenic selenide (TAS) crystals. Ishida and Kawano (1986) have reported that a molten KOH etching reveals a very clear etch pit on the (001) GaAs crystal. They have found that the etch pit shapes depend on the Burgers vectors of these dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…He also developed an etch pit reagent and to analyze the effects of thermal stress on the shapes and sizes of etch pits in thallium arsenic selenide (TAS) crystals. Ishida and Kawano (1986) have reported that a molten KOH etching reveals a very clear etch pit on the (001) GaAs crystal. They have found that the etch pit shapes depend on the Burgers vectors of these dislocations.…”
Section: Introductionmentioning
confidence: 99%